2012
DOI: 10.1080/03601234.2012.646173
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of organochlorine pesticides and polychlorinated biphenyls residues in vegetables, grain and soil from organic and conventional farming in Poland

Abstract: Organic and conventional crops were studied by identifying the relationship between persistent organic pollutants in cereals, vegetables and soil. The residues of organochlorine pesticides and polychlorinated biphenyls (PCBs) were determined in grains (rye and wheat), vegetables (carrots and beets) and soil collected from the fields. PCB residues recorded in the beets from organic farming were as high as 3.71 ppb dry weight (dry wt.), while in the soil from conventional farming of beets 0.53 ppb dry wt. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Atmospheric deposition that involves uptake of both wet and dry contaminated particulates onto exposed plant surfaces and through uptake of airborne vapours by aerial plant parts via the stomata has been documented as another pathway [79]. The study conducted by [80] in Poland showed that PCBs can still be detected in soil and vegetables either from organic or conventional farming. The result from that study further showed that PCBs in beets harvested from organic farm were high when compared with conventional farming system used.…”
Section: Polycyclic Aromatic Hydrocarbons (Pahs) and Polychlorinated mentioning
confidence: 99%
“…Atmospheric deposition that involves uptake of both wet and dry contaminated particulates onto exposed plant surfaces and through uptake of airborne vapours by aerial plant parts via the stomata has been documented as another pathway [79]. The study conducted by [80] in Poland showed that PCBs can still be detected in soil and vegetables either from organic or conventional farming. The result from that study further showed that PCBs in beets harvested from organic farm were high when compared with conventional farming system used.…”
Section: Polycyclic Aromatic Hydrocarbons (Pahs) and Polychlorinated mentioning
confidence: 99%
“…The typical half-life of residues detected in organic fields ranged from 100 days to more than a year. Although synthetic pesticides are not applied under organic farming (Reganold and Wachter, 2016) soils under organic farming may contain pesticide residues (Witczak and Abdel-Gawad, 2012). The European Commission requires a conversion time of two years of organic management before certification for annual crops (EC 2008b), which means that the content of very persistent compounds in soil (DT 50 > 1 year) at the time an organic crop is finally harvested will be 1/4 of the content that the crop would have had at the start of the organic conversion.…”
Section: Organic Agriculturementioning
confidence: 99%
“…Persistent organic pollutants (POPs) are organic pollutants that are very toxic, stable and persist for long period with adverse effect on human and the environment. They could also accumulate in aquatic lives [2,4,[6][7]. POPs are of great concern and a treaty was signed in Stocholm, Sweden on May 2001 on the eradication of these initial 12 POPs known as -dirty dozen‖ [18].…”
Section: Persistent Organic Pollutantsmentioning
confidence: 99%
“…These chemicals have severe effect on the ecosystem and water bodies [4].They could be threat to human and aquatic systems and resist environmental breakdown [5]. They are not easily degradable and they persist in the environment for a long time [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%